Edukasi Efesiensi Logistik dalam Pengelolaan Sampah Berkelanjutan di SMK Perbankkan Riau - Tanjung, Lailatul Syifa; Hardianti, Sri; Gustiana, Etri (Journal of Social and Community Service, 2025)
Effective waste management requires the support of an efficient logistics system, especially in school environments that generate waste on a daily basis. This community service activity aimed to provide education on logistics efficiency in sustainable waste management to students of SMK Perbankkan Riau. The methods used included socialization, interactive discussions, waste management supply chain simulations, and assistance in implementing the 3R system (Reduce, Reuse, Recycle). The results showed an 85% increase in students’ understanding of green logistics concepts, waste collection management, and waste reduction. In addition, the school has begun implementing waste segregation at the source, efficient transportation scheduling, and the processing of organic waste into compost. This activity is expected to serve as an initial step toward fostering an environmentally conscious culture and logistics efficiency in schools.